Semiotics : the basics - Chandler, Daniel (Routledge, 2007)
This updated second edition provides a clear and concise introduction to the key concepts of semiotics in accessible and jargon-free language. With a revised introduction and glossary, extended index and suggestions for further reading, this new edition provides an increased number of examples including computer and mobile phone technology, television commercials and the web. Demystifying what is a complex, highly interdisciplinary field, key questions covered include: What is a sign? Which codes do we take for granted? How can semiotics be used in textual analysis? -- What is a text? -- publisher description